Estimating the government health-care costs of treating pesticide poisoned and pesticide self-poisoned patients in Sri Lanka. Issue 1 (1st January 2019) - Ahrensberg, Hannah; Madsen, Lizell B.; Pearson, Melissa; Weerasinghe, Manjula; Eddleston, Michael; Jayamanne, Shaluka; Hansen, Kristian S.; Ariyarathna, Vindya; Rajapaksha, Sandamali; Konradsen, Flemming
ABSTRACT: Background : Pesticide self-poisoning as a method of suicide is a major global health problem. Objectives : To estimate the cost and per patient cost of treating pesticide self-poisoning at different hospital levels in a Sri Lankan district, and to examine the distribution of cost components. Another objective was to investigate changes in total cost of treatment of pesticide poisoning for all causes at different administrative levels in Sri Lanka in 2005 and 2015. Methods : The economic framework was a costing analysis, adopting a government perspective. Cost data were collected prospectively over a 4-month period in 2016 for patients admitted for pesticide self-poisoning to six hospitals in the Anuradhapura District. Assumption-based scenario analyses were run to determine changes in total pesticide poisoning treatment costs. Results : We included 67 self-poisoned patients in the study. The total cost of treatment was US 5, 714 at an average treatment cost of US 85.3 (9.7–286.6) per patient (across all hospital levels). Hospital costs constituted 67% of the total cost for treating self-poisoning cases and patient-specific costs accounted for 29%. Direct cost of patient hospital transfer constituted the smallest share of costs (4%) but accounted for almost half of the total costs at primary level. The estimated total cost of treating all causes of pesticide poisoning in Sri Lanka was US 2.5 million or 0.19% of the total government health expenditure (GHE) in 2015. Conclusion : Our findings indicate that the average per patient cost of pesticide self-poisoning treatment has increased while the total cost of pesticide poisoning treatment as a percentage of the total GHE in Sri Lanka has declined over the past decade. A continuous focus on banning the most hazardous pesticides available would likely further drive down the cost of pesticide self-poisoning and pesticide poisoning to the government.